DEVELOPMENT OF NATURAL AND MODIFIED GUM BASED SUSTAINED-RELEASE FILM-COATED TABLETS CONTAINING POORLY WATER-SOLUBLE DRUG - SHUKLA, AJAY KUMAR; SINGH BISHNOI, RAM; KUMAR, MANISH; JAIN, C.P. (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The objective of this work was to the development of natural and modified gum based sustained-release film-coated tablets containing poorly water-soluble drug. Methods: Tamarind seed gum (TSG), fenugreek seed gum (FSG), sodium trimetaphosphate, hydroxypropyl methylcellulose (HPMC), sodium alginate (SA), and nifedipine (NFD) were used. The core tablets of nifedipine were prepared and evaluated for weight, diameters, thickness, hardness, and disintegration time. The core tablets were coated using 2% w/v solution of TSG, MTSG, FSG, and MFSG. The in vitro release rate of drug from these coated tablets was compared with the release rate of drug from the tablets coated with 2% w/v of HPMC. Results: The tablets coated with natural and modified TSG sustained the release of the drug up to 11 h and 14 h, respectively, and natural and modified FSG sustained release the drug up to 9 h and 11 h, respectively. The tablets coated with HPMC sustained released the drug up to 15 h. The drug release profile of tablets coated with modified TSG was comparable to the release profile of tablets coated with HPMC. Conclusion: On the basis of the release profile, it is concluded that unmodified and modified TSG can be used as release rate-controlling membrane.